Identification of proteins capable of metal reduction from the proteome of the Gram‐positive bacterium D esulfotomaculum reducens MI ‐1 using an NADH ‐based activity assay - Anne Elyse Otwell; Robert W. Sherwood; Sheng Zhang; Ornella D. Nelson; Zhi Li; Hening Lin; Stephen J. Callister; Ruth E. Richardson (Environmental Microbiology, 2015)
Summary Understanding of microbial metal reduction is based almost solely on studies of G ram‐negative organisms. In this study, we focus on D esulfotomaculum reducens MI ‐1, a G ram‐positive metal reducer whose genome lacks genes with similarity to any characterized metal reductase. Using non‐denaturing separations and mass spectrometry identification, in combination with a colorimetric screen for chelated F e( III )‐ NTA reduction with NADH as electron donor, we have identified proteins from the D . reducens proteome not previously characterized as iron reductases. Their function was confirmed by heterologous expression in E scherichia coli . Furthermore, we show that these proteins have the capability to reduce soluble C r( VI ) and U ( VI ) with NADH as electron donor. The proteins identified are NADH : flavin oxidoreductase ( D red_2421) and a protein complex composed of oxidoreductase flavin adenine dinucleotide/ NAD ( P )‐binding subunit ( D red_1685) and dihydroorotate dehydrogenase 1B ( D red_1686). D red_2421 was identified in the soluble proteome and is predicted to be a cytoplasmic protein. D red_1685 and D red_1686 were identified in both the soluble as well as the insoluble protein fraction, suggesting a type of membrane association, although PSORTb predicts both proteins are cytoplasmic. This study is the first functional proteomic analysis of D . reducens and one of the first analyses of metal and radionuclide reduction in an environmentally relevant G ram‐positive bacterium.